Pengetahuan Lokal Dalam Epistemologi Relasional: Kajian Filsafat Kebudayaan - I Gede Mudana (Mudra Jurnal Seni Budaya, 2007)
local knowledge or invented tradition has to be related (“suturing”) to the globalization occurring these days. As a traditional capital, it has to be supported in the field of cultural studies. Using an example of tri hita karana in Bali, with its natural-human-religious relations, such knowledge is none other than a new paradigm called relational epistemology. A postmodern cultural studies, through the epistemology and its binary-opposition way, tries to ignore every opposition and contradiction in the modern life (modernity).